Pengendalian Penyakit Layu Fusarium pada Tanaman Cabai Besar (Capsicum annuum L.) dengan Kompos dan Pupuk Kandang yang dikombinasikan dengan Trichoderma sp. di Rumah Kaca - SUTARINI, NI LUH WAHYU; SUMIARTHA, I KETUT; SUNITI, NI WAYAN; SUDIARTA, I PUTU; WIRYA, G.N.ALIT SUSANTA; UTAMA, MADE SUPARTHA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2015)
ABSTRACT Utilization of Trichoderma sp. combined with compost and manure to controlling Fusarium wilt disease on long chilli (Capsicum annuum L.) in greenhouse This study aims to determine the effectiveness of Trichoderma sp. combined with compost and manure to controlling Fusarium wilt disease in long chilli (Capsicum annuum L.). Laboratory studies conducted at the Laboratory of Plant Pathology Faculty of Agriculture, University of Udayana and field research conducted in the greenhouse in the village Pancasari Sukasada Buleleng Subdistrict. The experimental design used was completely randomized designs (CRD) with five treatments were repeated 5 times, each treatment consisted of 5 polybag. The treatments used in this study are Po: control (soil + F. oxysporum f.sp. capsici treatment); P1: compost + soil + F. oxysporum f.sp. capsici; P2: compost + Trichoderma sp. + soil + F. oxysporum f.sp. capsici; P3: cow manure + Trichoderma sp. + soil + F. oxysporum f.sp. capsici; and P4: chicken manure + Trichoderma sp. + soil + F. oxysporum f.sp. capsici The results showed that treatment of Trichoderma sp. able to inhibit the growth of F. oxysporum f.sp. capsici with a percentage of 86.05% when compared to the control treatment at 7 days after inoculation observation in vitro. Application of Trichoderma sp. in compost and manure (cow manure and chicken) were able to suppress Fusarium wilt disease in the greenhouse with the lowest percentage of disease were in P3 and P4 treatment by 4.0% in the observation of 16 week after planting compared with 48.0% of control. Further, the application of Trichoderma sp. in compost and manure (cow manure and chicken) have yields greater than the control (soil without Trichoderma sp.) Keywords: Trichoderma sp., F. oxysporum f.sp. capsici, long chili (Capsicum annuum L.), compost, cow manure, chicken manure